Testosterone Use in Adolescent Males: Current Practice and Unmet Needs - Vogiatzi, Maria (J Endocr Soc, 2020)
Testosterone replacement therapy (TRT) is routinely prescribed in adolescent males with constitutional delay of growth and puberty (CDGP) or hypogonadism. With many new testosterone (T) formulations entering the market targeted for adults, we review current evidence and TRT options for adolescents and identify areas of unmet needs. We searched PubMed for articles (in English) on testosterone therapy, androgens, adolescence, and puberty in humans. The results indicate that short-term use of  T enanthate (TE) or oral  T undecanoate is safe and effective in inducing puberty and increasing growth in males with CDGP. Reassuring evidence is emerging on the use of transdermal  T to induce and maintain puberty. The long-term safety and efficacy of TRT for puberty completion and maintenance have not been established. Current  TRT regimens are based on consensus and expert opinion, but evidence-based guidelines are lacking. Limited guidance exists on when and how  T should be administered and optimal strategies for monitoring therapy once it is initiated. Only  TE and  T pellets are US Food and Drug Administration approved for use in adolescent males in the United States. Despite the introduction of a wide variety of new  T formulations, they are designed for adults, and their metered doses are difficult to titrate in adolescents. In conclusion, TRT in adolescent males is hindered by lack of long-term safety and efficacy data and limited options approved for use in this population. Additional research is needed to identify the route, dose, duration, and optimal timing for TRT in adolescents requiring androgen therapy.